Model Sistem Informasi Top Up Item Game Berbasis Website - Tri Setyo Budi; Agung Purwanto (STMIK Banjarbaru, 2022)
The customer service system that still uses chat message-based communication media at HayukStore21 (a company engaged in the sale of game items) causes slow service to customers, and narrows the range of product promotion areas. This research develops a web-based information system that can be used to manage and present product data, order and sell products online, as well as become a media for product promotion, so as to simplify the process of customer ordering and store sales, and expand the product marketing coverage area. System development refers to the stages in the SDLC (Software Development Life Cycle) model, using the HTML, PHP, CSS, Java Script and HeidSQL database programming languages, tested on the Laragon web server. Aspects of application system functionality were tested through a User Test of 10 respondents. The test results show that 90% of respondents agree that the system developed can make it easier to find out product availability, order/shopping, find out jockey profiles, confirm payments, and make it easy to operate the application system.Keywords: Software; Promotion; Sales; Software Development Life Cycle; User Acceptance Test AbstrakSistem layanan pelanggan yang masih menggunakan media komunikasi berbasis chat message pada HayukStore21 (perusahaan yang bergerak di bidang jasa penjualan item game) menyebabkan pelayanan kepada pelanggan menjadi lambat, serta jangkauan area promosi produk menjadi sempit. Penelitian ini mengembangkan sistem informasi berbasis web yang dapat digunakan mengelola dan menyajikan data produk, pemesanan dan penjualan produk secara online, serta menjadi media promosi produk, sehingga dapat mempermudah proses pemesanan pelangaan dan penjualan pihak store, dan memperluas area jangkauan pemasaran produk. Pengembangan sistem merujuk pada tahapan-tahapan dalam model SDLC (Software Development Life Cycle), menggunakan bahasa pemprograman HTML, PHP, CSS, Java Script dan database HeidSQL, diuji pada web Server Laragon. Aspek-aspek fungsionalitas sistem aplikasi diuji melalui Uji User terhadap 10 responden. Hasil pengujian menunjukkan 90% responden setuju bahwa sistem yang dikembangkan dapat mempermudah dalam mengetahui ketersediaan produk, pemesanan/berbelanja, mengetahui profile penjoki, mengonfirmasi pembayaran, serta mudah dalam pengoperasian sistem aplikasi.